Effect of Different Emulsifiers on the Surface Properties of 2-Hydroxypropylmethacrylate - Azizinezhad, Fariborz; Haroutiounian, Romic; Abdouss, Majid (Asian Journal of Chemistry, 2010)
The application areas of micelle-forming surfactants largely depends on surface properties of their aqueous solutions and on their emulsifying and stabilizing abilities. In this study, the effect of 2-hydroxypropyl-methacrylate (2-HPMA) on the stability of emulsion system with different emulsifiers and its distribution on toluene-water system, surface tension, surface enthalpy, surface entropy and half-decay time have been investi-gated. Results showed that: